Peranan Manajemen Perencanaan Pembangunan Desa Terhadap Partisipasi Masyarakat Di Kecamatan Gantarangkeke Kabupaten Bantaeng - Sangkala Irwan; Dasmaniar Dasmaniar; Jusran Jusran (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
This study aims to analyze the role of village development planning management on community participation in Gantarangkeke Subdistrict, Bantaeng Regency. Village development planning management in this study focuses on three main aspects, namely community empowerment, coordination, and program socialization. The research uses a quantitative approach supported by qualitative data. Data collection was carried out through observation, interviews, questionnaires, and documentation. The research population consisted of the community and government officials, with proportional sampling. Data analysis was performed using descriptive analysis and multiple linear regression. The results of the study indicate that community empowerment, coordination, and program socialization simultaneously have a positive effect on community participation in village development planning. Partially, community empowerment is the most dominant factor in encouraging community participation. These findings indicate that the success of village development planning is largely determined by the quality of planning management that can enhance community capacity, strengthen coordination among stakeholders, and optimize the dissemination of development program information. Therefore, enhancing the role of village development planning management is a crucial strategy in achieving participatory and sustainable village development planning.